Durum wheat grain production, grain quality, and plant nutrient concentration in response to different residue levels from two biannual crop rotations. (16th March 2021) - Hirzel, Juan; Undurraga, Pablo; León, Lorenzo; Panichini, Marcelo; Carrasco, Jorge; González, Jorge; Matus, Iván
Abstract: Residue incorporation in agriculture associated with crop rotation, benefits the environment, soil fertility, and crop production. However, the benefits of conservation agriculture practices in soil fertility and crop yield increases come up after several years. To study durum wheat ( Triticum turgidum L.) crop production under conservation agriculture with incorporation of residues a biannual rotation experiment was conducted in a volcanic soil in south-central of Chile.The experiment consisted was comprised of two crops, canola ( Brassica napus L.) and bean ( Phaseolus vulgaris L.), and four levels of residue incorporation (0%, 50%, 100%, and 200% of generated residue). Results indicated that grain yield, grain P, and residue K concentrations were higher when the previous crop was bean. Sedimentation values (SDS test), yellowness values (b), grain N concentration, grain and residue Ca concentrations, were higher when the previous crop was canola. The different leves of applied residue for the previous crop only presented effect on sedimentation values and yellowness values. Even though to obtain consistent results about the effect of different residue levels on a crop rotation experiments a larger number of crops cycles is required, the present work showed relevant results in a short time crop rotation. Highlights: Bean pre-crop increases durum wheat grain yield respect to canola crop in short-time rotations. Canola pre-cop increases sedimentation and yellowness value in durum wheat grain.